Connected Grundy Hop Dominating Sequences in Graphs (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we introduce and do an initial investigation of a variant of Grundy hop domination in a graph called the connected Grundy hop domination. We show that the connected Grundy hop domination number lies between the connected hop domination and Grundy hop domination number of a graph. In particular, we give realization results involving connected hop domination, connected Grundy hop domination, and Grundy hop domination numbers. Moreover, we determine the connected Grundy hop domination numbers of some graphs.
Keywords: connected Grundy dominating sequence; Connected Grundy domination number